An integrated project of entrepreneurship and innovation in engineering education - Soares, Filomena (2013)
This paper presents a new line of project based learning in the School of Engineering of University of Minho: the Innovation and Entrepreneurship Integrated Project (IEIP). Four groups, each one composed of students from different engineering integrated master courses – Mechanical, Industrial Electronics and Computers, Polymer, Industrial Management – compete against each other in developing or improving commercial products manufactured by actual industries. There have been so far five editions of the IEIP, with five different companies and five diverse products, however, all these products included components that required knowledge from all the engineering courses involved. Only with the cooperation between the students of the various courses that compose each multidisciplinary team, the success is attainable. As each student has to deal with various engineering scopes, students’ technical skills are greatly enlarged and they acquire a multidisciplinary knowledge that was not possible in another way. Their soft skills like project management, teamwork, communication ability and personal development, which are valuable requisites for their future employers, are also improved. The participating industries also take advantage of the project: the groups competing against each other act as a multiskilled work force, actually making proposals capable of improving their products, their efficiency, and reducing costs.